E-implementation: A time-based approach to extracting value from e-business - Wilding, Richard D. (Sckc Cranfield University, 2001)
“Too many stores….get up a nice web site. They get people interested in their products, but haven’t thought about how they are going to get their products to their customers. Even when they…got online orders right, there was a 75% chance that goods wouldn’t arrive on time.” This observation was made by “Time Magazine” in December 1999. Recent experiences of the author further confirm that the dream of e-commerce is in some areas an e-nightmare. For example, an attempt to order car catalogues from five of the leading automotive manufacturers through their web-sites resulted in no response from two manufacturers, one organisation sent a catalogue for the wrong model, another sent a letter saying they did not know what catalogue was requested and would therefore send details of their complete model range (which, incidentally, never arrived). Only one organisation sent the catalogue requested.